Elite football of 2030 will not be the same as that of 2020: Preparing players, coaches, and support staff for the evolution - Nassis, G. P.; Massey, A.; Jacobsen, P.; Brito, J.; Randers, M. B.; Castagna, C.; Mohr, M.; Krustrup, P. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Modern elite football is getting more and more demanding in terms of the numbers of matches played during the season that may add extra physical and mental load to the players. A top level European team used to play around 50 matches in the 2008/2009 season, and this number has increased to around 60 in the 2018/2019 season. In addition, for the most outstanding players, we also have to add the friendly matches as well as the international fixtures to the total. This may result in more than 70 matches played per season.1 The UEFA Elite Club injury study with 36 top European clubs reported a 2.5-fold increase in training and match time between the 2001/2002 and 2013/2014 season,2 and this constitutes an elevated workload for the players.